How Different Are Population Movements between Weekdays and Weekends: A Complex-Network-Based Analysis on 36 Major Chinese Cities - Chengyue Zhang (MDPI AG, 2021)
With the rapid development of Information and Communications Technology (ICT) and transportation infrastructure, the flows of people between cities have become the cornerstone of shaping regional integration. Although research studies about the movement of people have aroused widespread interest in academia, research about the temporal and spatial dynamics of daily mobility between cities is sparse, which is called the temporal heterogeneity of mobility between cities. This research aims to study the temporal and spatial changes (Heterogeneity) of population mobility between cities, using big data obtained through China Unicom, in terms of mapping the spatial network of population mobility and complex network analysis, from which the following findings emerge: (1) On weekends, the gap between cities in the number of floating population flow and the capacity of transferring population has become smaller, indicating that there is better coordination between cities on weekends. (2) There are huge differences in population flow between cities, which reflects the imbalance of urban development, population is more concentrated in cities with higher level of development. (3) The heterogeneity of population flow between cities at weekdays and weekends is closely related to the city’s hierarchy, which can help us study the hierarchical structure of China’s cities from a dynamic perspective. The paper emphasizes the importance of researching heterogeneity issues, clarifies the difference between the heterogeneity of weekdays and weekends and the heterogeneity involved in previous population research fields in terms of population flow and deficiencies in research.